Vascular response to the microcirculation in the fingertip by local vibration with varied amplitude - Mu, Lizhong; Sun, Aoran; Chen, Youqiang; Chen, Huimin; Li, Jianda; Linghu, Bingqi; Zhou, Hang; Chi, Qingzhuo; Luan, Xiaofeng; Pan, Yue (Frontiers in Bioengineering and Biotechnology, 2023)
It has been reported that long-term hand-transmitted vibration work is likely to cause hand peripheral circulation dis-orders, leading to the occurrence of vibration disease, mostly in the upper limb ends. In order to investigate the effect of local vibration intensity on the vascular response to the microcirculation of the finger, in this study we performed hand-transmitted vibration experiments combined with laser Doppler flowmetry (LDF) to measure the blood perfu-sion signals of fingertips in the vibrated hand and the contralateral middle finger under the same frequency and dif-ferent amplitude vibration, and to analyze the changes of microcirculatory blood perfusion levels in the fingers, and to investigate the effects of vibration stimulation on the endothelial, neural and myogenic regulatory frequency ranges of fingertips based on wavelet analysis. Furthermore, the transparent silicone films were fabricated and cultured with vascular endothelial cell (EC), which will undergo the local vibration with varied amplitude. The expression of in-flammatory factors was detected in the ECs. The experimental results showed that low-frequency vibration leads to a decreased blood flow in fingertip, and the degree of reduction in fingertip blood flow increases as the amplitude gradually increases, and the period required for blood flow to return to normal level after hand-transmitted vibration gradually increases. The decrease in blood flow is more pronounced in the vibrating hand than in the contralateral hand. In addition, nuclear factor-κB (NF-κB) expression increased significantly with the increase of vibration ampli-tude. It means that the vibration stimulation with high amplitude caused the inflammatory reaction of ECs which will lead to the altered endothelial regulatory activity. The endothelial regulatory activity is closely related to the blood perfusion in the microcirculation. It would be helpful for understanding the correlation between vibration stimulation and microcirculatory pathological changes of finger